2013
DOI: 10.1371/journal.pone.0056533
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Osteopontin in Patients with Thyroid Dysfunction

Abstract: Thyroid dysfunctions are common endocrine problems. They are often misdiagnosed, misunderstood, and frequently overlooked. These disorders affect almost every aspect of health. Most of them remain undetected because the clinical assessment alone lacks both sensitivity and specificity. As it is not sufficient enough we require the biochemical tests to confirm the diagnosis. As a consequence there is still great interest in new biomarkers that complement existing diagnostic tools. Osteopontin, a glycoprotein tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
(25 reference statements)
2
19
0
1
Order By: Relevance
“…The correlation study in TT genotype record a significant positive correlation between OPN and each fT4 and CYP4501A1 levels and this result agreed with [23] who found a positive correlation between osteopontin and thyroxin hormone and several studies reported that OPN was decreased in hypothyroidism [23], [24] which may be resulting from some processes of cell going on in the thyroid gland which probably decrease OPN receptor coexpression [23]. The significant positive correlation between OPN and CYP450 1A1 levels in this study accordance with [23], [25] who reported that CYP450 and OPN were decreased in hypothyroidism patients and this decreasing in CYP450 level may be because the low level of thyroid hormone in hypothyroidism patients which is responsible for regulation of expression of CYP through its control on levels of cellular CYP reductase, which had the ability to inactivate CYPs [26].…”
Section: Discussionsupporting
confidence: 84%
“…The correlation study in TT genotype record a significant positive correlation between OPN and each fT4 and CYP4501A1 levels and this result agreed with [23] who found a positive correlation between osteopontin and thyroxin hormone and several studies reported that OPN was decreased in hypothyroidism [23], [24] which may be resulting from some processes of cell going on in the thyroid gland which probably decrease OPN receptor coexpression [23]. The significant positive correlation between OPN and CYP450 1A1 levels in this study accordance with [23], [25] who reported that CYP450 and OPN were decreased in hypothyroidism patients and this decreasing in CYP450 level may be because the low level of thyroid hormone in hypothyroidism patients which is responsible for regulation of expression of CYP through its control on levels of cellular CYP reductase, which had the ability to inactivate CYPs [26].…”
Section: Discussionsupporting
confidence: 84%
“…Another novel cytokine is osteopontin (OPN), first discovered in 1986 in osteoblasts, but not until recently has its role in AID been further elucidated. OPN is released by various cell types, including chondrocytes, dendritic cells, T cells, and macrophages, after stimulation by pro-inflammatory events or cytokines (i.e., angiotensin II, TGF-β, TNF-α, IL-1b, nitric oxide, hyperglycemia, and hypoxia) [ 90 ]. It exerts its effects via the NF-κB pathway and consecutive production of IFN-γ and IL-12 stimulating Th1 cells.…”
Section: Main Textmentioning
confidence: 99%
“…It does so via its interaction with the ectodomain of integrin α v β 3. A clinical study has demonstrated that thyroid hormone increases OPN production [ 51 ]. Thus, it is possible that the thyroid hormone effect on P-gp may also have a contribution from increased availability of OPN for interaction with α v β 3 that is thyroid hormone-directed.…”
Section: Possible Mechanisms By Which Tetrac and Agonist Thyroid Hmentioning
confidence: 99%